PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS (TGT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS VII - Anggraini, Rini Kusuma; Sulaiman, Raden; Rochmatin, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this research is to describe the learning outcomes of students after the teacher uses the Teams Games Tounaments (TGT) learning method. The method used in this research is the learning outcome assessment method. The use of learning outcome tests is required as the research instrument for data collection. This research is a quantitative descriptive research. This is caused by the use of data analysis techniques using descriptive statistics. Before using the cooperative learning model of Teams Games Tournaments for students who obtained scores in the 86-100 range, 5 students with a percentage of 15.635% obtained passing grades. Meanwhile, after using the cooperative learning model of Teams Games Tournaments, there were 24 students who obtained passing grades with a percentage of 75%. The process of learning mathematics by applying the cooperative learning model of Team Game Tournament (TGT) can improve students' learning outcomes in mathematics.